Harmonization of income taxation of individuals in the Eurasian economic union countries - Yu. D. Shmelev (Вестник университета, 2019)
The development trends and the state of income tax systems in the world and the countries of the Eurasian Economic Union have been analyzed. Their similarities and differences have been revealed. The problem of harmonization of the legislation of income taxation of individuals has been considered. The assessment of justice and efficiency of the existing systems of income taxation in the countries of the Eurasian Economic Union has been carried out. The concept of harmonization has been proposed, which allows not only to unify the laws of the Eurasian Economic Union countries, but also to ensure an increase of the efficiency and fairness of the system of income taxation of individuals.